2016
DOI: 10.1177/0144598716680141
|View full text |Cite
|
Sign up to set email alerts
|

History matching of channel reservoirs using ensemble Kalman filter with continuous update of channel information

Abstract: Ensemble Kalman filter (EnKF) has been widely studied due to its excellent recursive data processing, dependable uncertainty quantification, and real-time update. However, many previous works have shown poor characterization results on channel reservoirs with non-Gaussian permeability distribution, which do not satisfy the Gaussian assumption of EnKF algorithm. To meet the assumption, normal score transformation can be applied to ensemble parameters. Even though this preserves initial permeability distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…DCT is also used to extract the main information of a static model in a history matching area [27][28][29][30][31][32][33][34][35]. After original data are transformed to coefficients of discrete cosine functions, the coefficients are arranged in descending order of frequencies of cosine functions.…”
Section: Combined Distancementioning
confidence: 99%
See 1 more Smart Citation
“…DCT is also used to extract the main information of a static model in a history matching area [27][28][29][30][31][32][33][34][35]. After original data are transformed to coefficients of discrete cosine functions, the coefficients are arranged in descending order of frequencies of cosine functions.…”
Section: Combined Distancementioning
confidence: 99%
“…The selection of a subset of DCT coefficients depends on the objective of the research. For example, to characterize channel reservoirs, several papers applied DCT to permeability data to extract only the main channel trends in the ensemble models with low frequencies' coefficients [27][28][29][30][31][32]34,35]. The channel trends in reservoirs can be described with only a small number of coefficients.…”
Section: + ( − 3) =mentioning
confidence: 99%
“…The coefficients are sorted in descending order from the top left, capturing the overall trend of channel patterns, to bottom right, delineating details in channel patterns. Previous studies have shown that non-Gaussian channel patterns can be reproduced sufficiently via inverse transform of essential DCT coefficients [18,28,35]. Updating the truncated DCT coefficients can yield a calibrated model set.…”
Section: Extraction Of Geologic Features Using Discrete Cosinementioning
confidence: 99%
“…The empirical cumulative distribution function (CDF) of model parameter was transformed into the corresponding quantile in CDF of standard normal distribution. This approach is useful, because any distribution could be converted to a standard normal distribution, which satisfies the Gaussian assumption in ensemble-based methods [33,34]. DCT is a method of representing audio or image information as a sum of cosine functions of different frequencies.…”
Section: Modification Of Model Parametersmentioning
confidence: 99%
“…A lot of equiprobable models could make this matter worse, by increasing computing time. Some works calibrated the grid properties, e.g., grid permeability, facies ratio, or mean value of permeability allocated to each facies [33,34]. However, it was hard to directly modify parameters for geostatistics from dynamic data, due to high nonlinearity.…”
Section: Modification Of Model Parametersmentioning
confidence: 99%